x^3*y^3=-8 x^3+y^3=-7

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Примеры

Решение

Вы ввели [src]
 3  3     
x *y  = -8
$$x^{3} y^{3} = -8$$
 3    3     
x  + y  = -7
$$x^{3} + y^{3} = -7$$
Быстрый ответ
$$x_{1} = -2$$
=
$$-2$$
=
-2

$$y_{1} = 1$$
=
$$1$$
=
1
$$x_{2} = -2$$
=
$$-2$$
=
-2

$$y_{2} = - \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
-0.5 - 0.866025403784439*i
$$x_{3} = -2$$
=
$$-2$$
=
-2

$$y_{3} = - \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
-0.5 + 0.866025403784439*i
$$x_{4} = 1$$
=
$$1$$
=
1

$$y_{4} = -2$$
=
$$-2$$
=
-2
$$x_{5} = 1$$
=
$$1$$
=
1

$$y_{5} = 1 - \sqrt{3} i$$
=
$$1 - \sqrt{3} i$$
=
1 - 1.73205080756888*i
$$x_{6} = 1$$
=
$$1$$
=
1

$$y_{6} = 1 + \sqrt{3} i$$
=
$$1 + \sqrt{3} i$$
=
1 + 1.73205080756888*i
$$x_{7} = - \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
-0.5 - 0.866025403784439*i

$$y_{7} = -2$$
=
$$-2$$
=
-2
$$x_{8} = - \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
-0.5 - 0.866025403784439*i

$$y_{8} = 1 - \sqrt{3} i$$
=
$$1 - \sqrt{3} i$$
=
1 - 1.73205080756888*i
$$x_{9} = - \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
-0.5 - 0.866025403784439*i

$$y_{9} = 1 + \sqrt{3} i$$
=
$$1 + \sqrt{3} i$$
=
1 + 1.73205080756888*i
$$x_{10} = - \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
-0.5 + 0.866025403784439*i

$$y_{10} = -2$$
=
$$-2$$
=
-2
$$x_{11} = - \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
-0.5 + 0.866025403784439*i

$$y_{11} = 1 - \sqrt{3} i$$
=
$$1 - \sqrt{3} i$$
=
1 - 1.73205080756888*i
$$x_{12} = - \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
-0.5 + 0.866025403784439*i

$$y_{12} = 1 + \sqrt{3} i$$
=
$$1 + \sqrt{3} i$$
=
1 + 1.73205080756888*i
$$x_{13} = 1 - \sqrt{3} i$$
=
$$1 - \sqrt{3} i$$
=
1 - 1.73205080756888*i

$$y_{13} = 1$$
=
$$1$$
=
1
$$x_{14} = 1 - \sqrt{3} i$$
=
$$1 - \sqrt{3} i$$
=
1 - 1.73205080756888*i

$$y_{14} = - \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
-0.5 - 0.866025403784439*i
$$x_{15} = 1 - \sqrt{3} i$$
=
$$1 - \sqrt{3} i$$
=
1 - 1.73205080756888*i

$$y_{15} = - \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
-0.5 + 0.866025403784439*i
$$x_{16} = 1 + \sqrt{3} i$$
=
$$1 + \sqrt{3} i$$
=
1 + 1.73205080756888*i

$$y_{16} = 1$$
=
$$1$$
=
1
$$x_{17} = 1 + \sqrt{3} i$$
=
$$1 + \sqrt{3} i$$
=
1 + 1.73205080756888*i

$$y_{17} = - \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} - \frac{\sqrt{3} i}{2}$$
=
-0.5 - 0.866025403784439*i
$$x_{18} = 1 + \sqrt{3} i$$
=
$$1 + \sqrt{3} i$$
=
1 + 1.73205080756888*i

$$y_{18} = - \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
$$- \frac{1}{2} + \frac{\sqrt{3} i}{2}$$
=
-0.5 + 0.866025403784439*i
Численный ответ [src]
x1 = 1.00000000000000
y1 = -2.00000000000000
x2 = -2.000000000000004
y2 = 1.000000000001102
x3 = -2.00000000000000
y3 = 1.00000000000000
x4 = -2.000000000002318
y4 = 0.9999999999956066